2018
DOI: 10.1155/2018/1285823
|View full text |Cite
|
Sign up to set email alerts
|

Application of Food-Grade Proteolytic Enzyme for the Hydrolysis of Regenerated Silk Fibroin fromBombyx mori

Abstract: In vitro biodegradation of Bombyx mori silk fibroin (SF) was studied using food-grade proteolytic enzymes to replace acid hydrolysis. Based on the residual protein quantity and yield of amino acids (AAs) after enzymatic hydrolysis, we evaluated the proteolytic enzyme process of SF. FoodPro and Alcalase that are classified as alkaline proteases are selected as two of the best candidate enzymes for hydrolysis of SF. e activity of these enzymes exhibits a broad range of pH (6.5 to 9.0) and temperature (50°C to 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Consistent with our hypothesis, we confirmed in this study that GSDsup had the highest total polyphenol content and antioxidant activity ( Figure 4 ) and more small molecular weight peptides than GS, GSD, or GSDprec ( Supplementary Figure 1 ). In addition, we have shown that digestion of freeze-dried 5th instar 3rd-day larval powders with food-grade proteases increased small molecular weight peptides in the previous study ( 33 ), supporting our results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our hypothesis, we confirmed in this study that GSDsup had the highest total polyphenol content and antioxidant activity ( Figure 4 ) and more small molecular weight peptides than GS, GSD, or GSDprec ( Supplementary Figure 1 ). In addition, we have shown that digestion of freeze-dried 5th instar 3rd-day larval powders with food-grade proteases increased small molecular weight peptides in the previous study ( 33 ), supporting our results.…”
Section: Discussionsupporting
confidence: 92%
“…HongJam consists of approximately 70% crude proteins, 15% crude fatty acids, 3% crude ash, and 2% phytochemicals and vitamins ( 10 , 19 , 30 , 32 ). Recently, the Fibroin in silk fibers could reportedly be hydrolyzed by food-grade proteolytic enzymes ( 33 ). The FoodPro ® alkaline protease (FP ® AP) was efficiently used to hydrolyze the silk fiber Fibroin.…”
Section: Introductionmentioning
confidence: 99%
“…3.4 Antioxidant activity F2 had significantly higher (p < 0.05) scavenging activity than control due to the presence of Flavourzyme® which was known as a food-grade proteolytic enzyme (protease) (Joung et al, 2018). Protease targets protein to undergo enzymatic hydrolysis, producing antioxidant peptides and hydrolysate which are proton-donating substrates that act to scavenge DPPH radicals.…”
Section: Total Dietary Fibre (Tdf)mentioning
confidence: 99%
“…In addition, recent work has shown that broin hydrolysates impact the Nuclear Factor-kappa B (NF-kB) in ammatory pathway [6], which is an early stage cell signaling lynchpin to initiate in ammatory gene expression [23]. However, production of broin hydrolysates requires additional processing steps and reagents, which introduce complexity, cost, and potential contaminates (e.g., enzymes) to the nal product [24].…”
Section: Introductionmentioning
confidence: 99%